Hybridation naturelle entre les deux sous-espèces d'huîtres creuses Crassostrea gigas et Crassostrea angulata au sud de l'Europe - Huvet, Arnaud; Fabioux, Caroline; Lapegue, Sylvie; Boudry, Pierre (Actes Journées Conchylicoles, Ifremer Nantes, 3-4 avril 2001, 2001)
Crassostrea angulata and Crassostrea gigas, two cupped oysters of Asian origin (O'Foighil et al, 1998), have been introduced successively in Europe during the XVlth and the XXth century (Grizel et Héral, 1991). The present populations of C. angulata appear to be limited to the south of Spain and Portugal, whereas the distribution of C. gigas in Europe is rising because of the development of oyster farming. The distinction between the two subspecies in based on a RFLP marker of the mitochondrial genome (COI) which shows a strong genetic differentiation between the two subspecies populations (Boudry et al., 1998). On the contrary, the nuclear markers (microsatellites) showed a smaller genetic differentiation between them (Huvet et al, under press). The absence of a reproductive barrier between C. angulata and C. gigas, which has been demonstrated experimentally (Gaffney and Allen, 1993; Huvet, 2000), leads us to suspect some hybridization phenomenons between these two cupped oysters in the wild. In order to study these phenomenons, 9 populations have been sampled along the European Atlantic coast (France, Spain, Portugal). Crassostrea angulata et Crassostrea gigas, deux huîtres creuses d'origine asiatique (O'Foighil et al, 1998), ont été successivement introduites en Europe respectivement au cours du XVlème et du XXème siècle (Grizel et Héral, 1991). Les populations actuelles de C. angulata apparaissent restreintes au sud de l'Espagne et du Portugal, alors que la distribution européenne des populations de C. gigas s'accroît en raison du développement de l'aquaculture. La distinction entre ces deux sous-espèces est basée sur un marqueur RFLP du génome mitochondrial (COI) qui montre une forte différenciation génétique entre les populations des deux sous-espèces (Boudry et al., 1998). A l'inverse, des marqueurs nucléaires (microsatellites) ont montré une plus faible différenciation génétique entre ces mêmes populations (Huvet et al, sous presse). L'absence de barrière reproductive entre C. angulata et C. gigas a ...